In vitro characterization of an injectable in situ forming composite system for bone reconstruction. (September 2015) - Dorati, R.; Colonna, C.; Genta, I.; De Trizio, A.; Modena, T.; Klöss, H.; Conti, B.
Abstract: Injectable in situ forming composite scaffolds (ISFcG) have been prepared combining bovine bone substitute granules with a biodegradable and biocompatible thermogelling polymeric solution (chitosan). The presence of the organic component affects both physico-chemical features of ISFcG, as porosity, interconnectivity, mechanical properties and biofunctionality. The high water retention ability and the hydrophilic nature of the ISFcG polymer matrix promote the attachment and the infiltration of cells into the matrix and their growth. The polymeric component of ISFcG was susceptible to degradation during the in vitro incubation in simulated physiological conditions (DMEM pH 7.4, 37 °C). The degradation products did not present remarkable toxicity level, as the MTT data resulted to be constant. The stability study showed an excellent in vitro physical stability even after mechanical stress. These features make the ISFcG based on chitosan and bovine bone substitute granules an excellent injectable composite scaffold for bone tissue regeneration.